Enterprise Risk Management, the Balancing Act: Navigating Growth with Financial Health - Albert, Albert; Wahid, Ayi; Nengsih, Widya; Prastyaningsih, Nila (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to determine the effect of Enterprise Risk Management (ERM), Company Size (SIZE), Debt to Equity Ratio (DER) and Profitability (ROA) on Company Value at BUMN Commercial Banks on the Indonesia Stock Exchange. The data used is secondary data and the method used is multiple linear regression analysis using the SPSS 20 program to obtain a comprehensive picture of the relationship between one variable and another. The sample of this study consisted of 4 banks from 2012 - 2019 using saturated sampling as a sampling method. The results of this study indicate that the ERM, Company Size and Profitability variables have a significant effect on the Value sometimes with a significance level of less than 5%, while DER partially has no significant effect. The results of simultaneous regression analysis show that ERM, SIZE, DER and ROA together affect Firm Value. The coefficient of determination (Adjusted R Square) of the results of this study is 0.665, which means that the four variables are able to influence 66.50% and the rest is influenced by other proportions that are not variables in this study